Saúde mental e trabalho: prevalência de morbidade psiquiátrica e fatores associados, entre servidores municipais em licença médica, Goiânia-Goiás, 2010 - Mendonça, Mauro Elias (2013)
Introduction: Mental disorders (MD) have high morbidity and high load in the years lived with disability, reducing quality of life and producing large socioeconomic impact. Objective: To estimate the prevalence and potential factors associated with psychiatric morbidity of municipal employees on sick leave in Goiânia, Brazil, in 2010. Methods: Cross-sectional census study linking Human Resources System with records of licenses issued by the Medical Board municipality. Socio-demographic and occupational variables and duration of the associated removal by MD licenses were analyzed. The level of significance was set at <5%. Results: Among the 20,535 servers, 5,028 (24.5%) had at least one license, with 801 of these for psychiatric morbidity. In total 9,101 licenses, of which 1,569 were granted for MD. The MD represented the greatest burden of the total period of absence (22.1%) with 75% of the servers on leave for > 15 days. The prevalence of MD was 39.0 licensed servers/1.000 active servers, with 76.4 licenses/1.000 active servers. The prevalence of MD was higher among women and servers with primary or higher education level. There were differences in the leave of absence profile caused by DM between men and women regarding age, ethnicity, marital status and salary. In relation to work, there was a higher prevalence of MD on servers with double bond, length of service <3 years (probation) and with 11-20 years of work. The highest prevalence of MD among women, was found in positions of education and health, and, among men, in surveillance jobs. Mood disorders (25.4/1,000) and neurotic (16.9/ 1,000) were clusters of higher prevalence, with high co-morbidity between both. The diagnostic category of depression was more prevalent. Discussion and Conclusions: In the present study, the prevalence of MD was more than six times higher than the one found on workers of the general social security system in the country. The results confirm the relevance of MD in health of servers, and bring subsidies to boost promotion measures, surveillance and occupational health care. The need to deepen the study of psychosocial factors associated with high prevalence of psychiatric morbidity in the public sector and differences in gender and occupation was pointed out in this study.